Essential contents for software development process and software quality education. (1st January 2014) - Hwang, Sun-Myung
There are software engineering absences that cause the software quality and productivity increase problems during software development project. There exists necessity awareness of software engineering growth and professional software engineering manpower education. This paper introduces the software engineering standard curriculum to suggest manpower practical-use guide and to establish continuous growth to strengthen manpower ability and expertise. When performing the projects, we can suggest for software engineering professional acquisition and standard to solve them by using standard curriculum for software engineering, which can strengthen manpower capacity the organisational software engineering. This paper provides educational guideline of for software process and software quality.